Progress in age estimation based on DNA methylation - Yihang Huang; Shengqiu Qu; Yuanyuan Xiao; Hui Jian; Weibo Liang (Wolters Kluwer Medknow Publications, 2023)
In forensic practice, the age of suspects or victims is crucial information that aids in the resolution of cases. In recent years, age estimation based on DNA methylation has gained significant attention in forensic science. DNA methylation, an epigenetic marker, undergoes specific changes with age, making it a valuable tool for inferring the age of samples left at crime scenes. Therefore, the identification of age-related DNA methylation markers and the development of novel age estimation models are of great importance in forensic medicine. Numerous studies in the past decade have successfully established age estimation models based on DNA methylation, demonstrating excellent sensitivity and accuracy. To provide a comprehensive review, the authors of this paper conducted a systematic review of relevant articles published from 2012 to the present. We used keywords such as "forensic," "DNA methylation," and "age estimation" to retrieve pertinent articles from the Web of Science database. The review covers various aspects, including the sources of sample tissues used for age estimation, DNA methylation conversion methods, and different techniques for DNA methylation detection. In addition, the paper reviews the modeling methods for age estimation based on DNA methylation and factors that can influence DNA methylation. Overall, this review serves as a valuable reference for forensic genetics, offering insights into the latest advancements in age estimation using DNA methylation. As the field of forensic science continues to evolve, the integration of DNA methylation-based age estimation into practice is expected to enhance the accuracy and reliability of age determination in criminal investigations.